Let us assume the first number to be = x
Let us assume the second number to be = y
Then
x^2 - y^2 = 5
x^2 = y^2 + 5
And
3x^2 - 2y^2 = 19
Multiplying the first equation by -2, we get
- 2x^2 + 2y^2 = - 10
Now subtracting the two equations, we get
x^2 = 9
x = 3
Putting the value of "x" in the first equation, we get
(3)^2 - y^2 = 5
9 - y^2 = 5
y^2 = 4
y = 2
I hope that the procedure is clear enough for you to understand and this is the answer that you were looking for.
Answer:
f5ctctvvytvyvyvububub
Step-by-step explanation:
xrctcc5f5
Answer: x=-1, y=-8
Step-by-step explanation: solve for the first variable in one of the equations then subsitutte the result into the other equation
Answer:
ahhh......okay....but I can't see the question...or even the answer!!!
Step-by-step explanation:
I believe the answer is c